Synthesis and anion recognition properties of shape-persistent binaphthyl-containing chiral macrocyclic amides - Caricato, Marco; Leza, Nerea Jordana; Gargiulli, Claudia; Gattuso, Giuseppe; Dondi, Daniele; Pasini, Dario (Beilstein Journal of Organic Chemistry, 2012)
We report on the synthesis and characterization of novel shape-persistent, optically active arylamide macrocycles, which can be obtained using a one-pot methodology. Resolved, axially chiral binol scaffolds, which incorporate either methoxy or acetoxy functionalities in the 2,2' positions and carboxylic functionalities in the external 3,3' positions, were used as the source of chirality. Two of these binaphthyls are joined through amidation reactions using rigid diaryl amines of differing shapes, to give homochiral tetraamidic macrocycles. The recognition properties of these supramolecular receptors have been analyzed, and the results indicate a modulation of binding affinities towards dicarboxylate anions, with a drastic change of binding mode depending on the steric and electronic features of the functional groups in the 2,2' positions.
Keywords: amides; anion recognition; chirality; macrocycles; molecular switches; supramolecular chemistry